High-resolution historical emission inventories of crop residue burning in fields in China for the period 1990–2013 - Jing Li; Li, Yaqi; Bo, Yu; Shaodong Xie (Atmospheric Environment, 2016)
High-resolution historical emission inventories of crop residue burning in fields in China were developed for the period 1990–2013. More accurate time-varying statistical data and locally observed emission factors were utilized to estimate crop residue open burning emissions at provincial level. Then pollutants emissions were allocated to a high spatial resolution of 10 km × 10 km and a high temporal resolution of 1 day based on the Moderate Resolution Imaging Spectroradiometer (MODIS) Fire Product (MOD/MYD14A1). Results show that China’s CO emissions have increased by 5.67 times at an annual average rate of 24% from 1.06 Tg in 1990 to 7.06 Tg in 2013; the emissions of CO2, CH4, NMVOCs, N2O, NOx, NH3, SO2, PM2.5, OC, and BC have increased by 595%, 500%, 608%, 584%, 600%, 600%, 543%, 571%, 775%, and 500%, respectively, over the past 24 years. Spatially, the regions with high emissions had been notable expanding over the years, especially in the central eastern districts, the Northeastern of China, and the Sichuan Basin. Strong temporal pattern were observed with the highest emissions in June, followed by March to May and October. This work provides a better understanding of the spatiotemporal representation of agricultural fire emissions in China and can benefit both air quality modeling and management with improved accuracy.